Evaluation of the dioxin and furan formation thermodynamics in combustion processes of urban solid wastes - Moreno-Piraján, Juan Carlos; García-Ubaque, César Augusto; Fajardo, R.; Giraldo, Liliana; Sapag, Karim (Eclética Química, 2007)
Specific combustion programs (Gaseq, Chemical equilibria in perfect gases, Chris Morley) are used to model dioxin and formation in the incineration processes of urban solid wastes. Thanks to these programs, it is possible to establish correlations with the formation mechanisms postulated in li- terature on the subject. It was found that minimum oxygen quantities are required to obtain a significant formation of these compounds and that more furans than dioxins are formed. Likewise, dioxin and furan formation is related to the presence of carbon monoxide, and dioxin and furan distribution among its different compounds depends on the chlorine and hydrogen relative composition. This is due to the fact that an increased chlorine availability leads to the formation of compounds bearing a higher chlorine concentration (penta-, hexa-, hepta-, and octachlorides), whereas an increased hydrogen availability leads to the formation of compounds bearing a lower chlorine number (mono, di-, tri-, and tetrachlorides)